胃瘻造設患者様のトラブル改善を目指して - 宮本 晃揮; 村山 美香; 山本 三富美; 藤野 勝 (The Journal of Showa Hospital, 2007)
About 32% (19 customers) patients received percutaneous endoscopic gastrostomy tubes (PEG) at our nursing care ward. PEG could be more practical than nasal tubing nutrition because of no tube around his/her face and less tracheal obstruction or aspiration pneumonia, however a patient frequently pull out the PEG tubing, this movement allowed the penetrated area easy to infect. We tied to improve our methodology and succeeded by 2 cases. Mr. Y suffered from multiple cerebral infarction and cerebrovascular dementia, ex-perienced 4times of pulling out during 4 months of hospitalization. Tubing outlet was wounded and formed granulation tissue with exsudate. Diagnosis of Mr. M was multiple cerebral infarction and dementia. He ex-perienced 4 times of pulling out during 25 months. The outlet infected become dirty with exsudate. Strategy: Mitten-gloves were taken off, and the catheter was hide in the protector pocket. Patients become no care about hidden catheter and felt comfortable. The daily skin care turned into no erosion, no granulation and no exsu-date. As results, no patient received banding restrain in our ward and change PEG tube into mini-button. 当病棟の胃瘻造設の患者様は19名で全体の32%を占めている。　胃瘻は鼻腔チューブに比べ、不快感・合併症も少なく管理しやすいが、自己抜去や創部感染のトラブルが多い。そこで、２名を対象に、改善に取り組み、効果を得たので報告する。Ｙ氏：[多発性脳梗塞、脳血管性痴呆]、入院4ヶ月間で自己抜去４回を起こしていた。 ミトン手袋を着用するも１回自己抜去あり。合計5回の自己抜去により創部は発赤、肉芽形成、浸出液が出ており、バルンカテーテル16Fr挿入。　Ｍ氏：[多発性脳梗塞・痴呆]入院１年７ヶ月で、自己抜去４回、掻痒感を伴う皮膚疾患があり、テープによるカテーテルの固定が困難。創部は発赤はないが浸出液が多く、バルンカテーテル20Fr挿入。両氏への対策: 先ずミトンの手袋を外し、カテーテルを目に触れない様に胃瘻保護帯の中に納める事で自己抜去や保護帯を外す行為もなくなり結果的に、病棟内の抑制はゼロとなった。　スキンケア観察を続ける事で創部の発赤、肉芽形成、浸出液は軽減され、ミニボタンに交換も可能となった。